No Burmese Returning: Economics Across Myanmar-Thailand Border - Rhoden, T. F. (Thai Journal of East Asian Studies, 2015)
As Myanmar’s national politics change from a military authoritarian regime toward civilian rule, this paper seeks to understand whether Burmese emigrants abroad are starting to return home. By placing the specific case study of net migration flows across the Myanmar-Thailand land border into a larger study of all of net migration flows across all other land borders around the globe, a comparison can be made as to the direction and the amount of these net migration flows. We argue that, regardless of the political ituation, when surveying the top large-scale net migration flows of over 350,000 people, fairly simple economic indicators help us to predict that, ceteris paribus, the direction of any net igration flow will move from poorer to wealthier country. Material differences in wealth, however, do not help to predict the amount of that net migration flow. We conclude that because of prevailing magnitudes of material difference between Myanmar and Thailand, we see othing that suggests that Burmese migrants have started to return home in any large numbers.